Mobile Application for Anaemia Prevention and Prediction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The invention is a unique nutrient deficiency-preventing and managing mobile application that allows its user to detect the severity of their deficiencies by taking a picture of their fingernails using their mobile phone camera. Using this data, the app supplies the user with dietary and lifestyle recommendations. Provided that the user follows them, the app suggestions will significantly help the users lower their risk of nutrient deficiencies and overcome the condition altogether. If the deficiency is too severe for the user to overcome with dietary and lifestyle changes, the app will inform the user to seek medical intervention.